DOES ASPLENIUM FALCATUM EXIST IN THE PHILIPPINES? - Salgado, A. E. (Edinburgh Journal of Botany, 2016)
Plants commonly known as Asplenium falcatum in the Philippines and other parts of Southeast Asia represent a complex of closely related taxa. Because of the great variability of these plants, several names have been proposed over the years to refer to members of this complex in the Philippines. The name Asplenium falcatum has been used erroneously for superficially similar Philippine plants, which should be named Asplenium oxyphyllum Kunze.